THE ROLE OF MINDFUL PARENTING TO THE PARENTING STRESS IN MOTHERS WITH CHILDREN AT EARLY AGE - Kumalasari, Dewi; Fourianalistyawati, Endang (Jurnal Psikologi, 2020)
Parenting is an important process, and the processes in each phase are challenging, particularly during the phase of early childhood. The challenges in parenting could trigger parenting stress. The ability to give full attention to the conducted parenting process can help parents in coping the parental stress. The process of giving full attention to parenting activities is known as the mindful parenting concept. This study aims to determine the role of mindful parenting to parenting stress of mothers with a child at an early age. This study used a quantitative method.Â  A Mindfulness in Parenting Questionnaire (28 items, Î± = .915) and Parental Stress Scale (18 items, Î± = .705) were given to the respondents. The data was collected from 281 respondents (ages 21-54 years, M = 32.75, SD = 5), which was selected through incidental sampling methods. Based on the regression analysis, the results show that mindful parenting has a significant contribution to the low parenting stress levelÂ  in mothers with child at early age (R = -.260, R2 = .068, Î² = -0.119, F (1, 280) = 20.153, p < 0.01). This result suggests that mindful parenting skills can be an alternative way to reduce parental stress on mothers with a child in early childhood.